Analisis Pengaruh Faktor-Faktor Perilaku Konsumen terhadap Keputusan Pembelian Ulang Produk Simpanan Hari Raya - Rosa Norita; M. Shofiyuddin (Universitas Muhammadiyah Surabaya, 2025)
This study aims to test and analyze the influence of consumer behavior on the decision to repurchase holiday savings products abbreviated as Sahara. Consumer behavior itself consists of cultural factors, social factors, personal factors and psychological factors. The population in this study is members of KSPPS BMT Bahtera Pekalongan branch, and sampling is done using a simple random sampling technique. A sample of 90 members was obtained. To test the influence of the indepent variable on the dependent variable using multiple linear regression analysis on the SPSS program. The test results found that cultural and social factors had a positive and significant effect on the decision to repurchase Sahara products, personal factors had a negative and insignificant effect, and psychological factors had a positive and insignificant effect on the decision to repurchase Sahara products.